4-Hydroxybenzoic acid from hydrothermal pretreatment of oil palm empty fruit bunches – Its origin and influence on biomass conversion. (October 2016) - Rasmussen, Helena; Mogensen, Kit H.; Jeppesen, Martin D.; Sørensen, Hanne R.; Meyer, Anne S.
Abstract: An unknown major compound, characteristically occurring during processing of oil palm empty fruit bunches was identified with LC-DAD-ESI-MS/MS to be 4-hydroxybenzoic acid. Lignin from oil palm empty fruit bunches contains 4-hydroxybenzoic acid so a tempting conclusion was that the 4-hydroxybenzoic acid originated from lignin. However, another hypothesis to its origin was also tested. The route considered involves degradation of rhamnose to 5-methylfuran-2-carbaldehyde followed by reaction with formic acid. Experimental hydrothermal pretreatment of pure rhamnose in the presence of formic acid revealed that 5-methylfuran-2-carbaldehyde is in fact a degradation product from rhamnose, analogous to glucose degradation to 5-(hydroxymethyl)-2-furaldehyde. However, the subsequent step of carboxylation with formic acid to form 4-hydroxybenzoic acid was found not to take place in practice at realistic biomass hydrothermal pretreatment conditions. 5-methylfuran-2-carbaldehyde only differs from furfural by having an extra methyl group and the degradation route indicates that it may be a new important degradation compound to consider in other biomass feedstocks rich in deoxysugars such as rhamnose or fucose, e.g. pectin rich biomasses. Assessment of the influence of 4-hydroxybenzoic acid in the enzymatic hydrolysis of pretreated oil palm empty fruit bunches as well as its presence during fermentation showed that 4-hydroxybenzoic acid is not inhibiting or mediating neither on the enzymatic hydrolysis or fermentation in the quantified range from 0.1 g/L to 1 g/L, indicating an option for reaping the 4-hydroxybenzoic acid from the biomass liquor directly after hydrothermal pretreatment for biorefinery value-addition. Graphical abstract: Highlights: An unknown major compound, characteristic for oil palm empty fruits bunches, was identified to be 4-hydroxybenzoic acid. 4-hydroxybenzoic acid was found to derive from lignin; was presumably released during hydrothermal pretreatment. 4-hydroxybenzoic acid is not inhibitory to the enzymatic hydrolysis or the subsequent fermentation step. Rhamnose is degraded to 5-methylfuran-2-carbaldehyde analogous to glucose degradation to HMF. 5-methylfuran-2-carbaldehyde may be an important degradation compound from biomasses rich in pectin.